Transformational Leadership and Compensations Effect on Employee’s Performances by means of Job Satisfaction as Mediation Variable at CV. General Design Klungkung Regency - Putu Ayu Krisna Dewi; Ida Bagus Udayana Putra (Universitas Warmadewa, 2023)
Employees performance at company needs been noticed because it can affect to the company's performance. This study aims to analyze the effect of transformational leadership and compensation on employee’s performances by means of job satisfaction as mediation variable. The object of this study are all employees of CV. General Design totaling 40 people. The data are collected by using a questionnaire with five Likert scale and using Partial Least Square (PLS) as a data analyze. The results of this study indicated that transformational leadership had a positive and insignificant results on employee’s performances, but it had a positive and significantly effect to job satisfaction. Then compensation had a positive effect and significant to the job satisfaction and the employee’s performances. While job satisfaction affects positively and had no significant effect to the employee’s performances. In addition, job satisfaction is not a mediation of transformational leadership and compensation effect on the employee’s performances. For the further researchers are expected to add alternative constructs that affect to the employee’s performances besides transformational leadership, compensation, and job satisfaction. In addition, for the next researches, it should add more references related to research and hope this result can be used for reference to study on similar companies.